ANIMASI BUDIDAYA JAMUR TIRAM PADA RAFLESIA JAMUR KOTA BENGKULU - Hasan Ashari; Maryaningsih Maryaningsih; Dewi Suranti (Jurnal Media Infotama, 2014)
This study was conducted on January 25, 2014 until February 27, 2014 in the city of Bengkulu Raflesia Mushroom with a view to making the cultivation of oyster mushroom animated film created using 3D Studio Max, which is a software to create animated 3D movies. Based on the results of the study showed that it takes a simple 3D animation in order to facilitate the entrepreneurs and the public about how the oyster mushroom cultivation. Animated film made in 3D does not leave the original form of the cultivated mushroom itself, because 3D shapes that resemble the original shape. So that people who want to know the oyster mushroom cultivation, can see the animated movie.Keywords: Animation Oyster Mushroom Cultivation